Analisis Dampak Kualitas Pengungkapan Internet Financial Reporting Terhadap Nilai Perusahaan (Studi Pada Perusahaan Dalam Indeks Kompas100 Tahun 2014-2017) - Peggy Khairina Fauziah; Hendra Agustinus Marbun; Nirmala Purba (JAKPI - Jurnal Akuntansi, Keuangan & Perpajakan Indonesia, 2019)
Abstrak : Financial reporting plays important role of giving information about firm performance and helping investor deciding the investment that will affect firm value. Internet financial reporting disclosure as a way to display firm financial reporting and firm performance to stakeholder globally become an issue on its affect to the firm value. The objective of this study are to examine whether the quality of IFR disclosure affecting the firm value, are the firm with higher IFR disclosure quality have higher firm value than the firms with lower IFR disclosure quality. To robust the result of this study it use the firm size, and profitability as control variable. The sample of this study are 72 firms listed in KOMPAS100 Indonesia Stock Exchange Index on 2014-2017 define by purposive sampling method, the data was collected by combining qualitative and quantitative method do determine variable, and then processed using the statistical tool Eviews version 4 and then the results are presented in numbers and tables The multiple regression analysis result show that our quantitative measurement of IFR quality variable has positive effect to the firm value. Firms with higher IFR disclosure quality proven have higher firm value than the companies with lower IFR disclosure quality. This result implies that firms with higher IFR disclosure quality inform better information to the stakeholder and sends good signals for the investor so that helps in increasing the firm value.   Kata Kunci : Internet Financial Reporting, Disclosure, IFR Quality,  Firm Value